Application of innovative mechatronic systems in product design, development and production - Vasiljević, Saša; Rajković , Dragan; Đorđević, Milan; Kostić, Sonja; Stanojević, Milan (Journal of Production Engineering, 2024)
The application of mechatronic systems is very topical today. Today, mechatronic systems are applied in all areas, so today systems are also being developed that enable fast and simple production of products. Today's mechatronic systems that are supported by computers enable the development, easy and fast production of prototypes and products. Two technologies that are widely used are 3D printers and scanners. 3D printers allow a virtually developed product to be turned into a physical model, while the application of a 3D scanner allows a physical model to be turned into a virtual model on a computer. In this paper, a comparative analysis of two types of printers and their software was performed. They differ according to their working principle. In addition to the working principle, an example of the difference between the software used to write the G code to drive the printing process of 3D printer.